1998
DOI: 10.1038/sj.bjp.0702184
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of an H1 receptor‐mediated, zinc‐potentiated vasoconstrictor action of the histidyl dipeptide carnosine in rabbit saphenous vein

Abstract: 1 The contractile action of the dipeptide carnosine (b-alanyl-L-histidine), active as a Zn·carnosine complex (Zn·Carn), was investigated in isolated rings of rabbit saphenous vein (RSV) and was found to be antagonized by the H 1 antagonist mepyramine. 2 Mepyramine-sensitive, histamine-induced contractures in RSV, were smaller (73+0.1%) and less well sustained than carnosine-induced contractures. In the radioligand binding assay, the e ect of carnosine can be described as a function of Zn·Carn concentration wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Miller and O'Dowd have reported that, like histamine, carnosine directly activates smooth muscle histamine H 1 receptors to provoke vasoconstriction, but induces vascular relaxation through H 2 receptors . Ligand–receptor binding tests revealed that carnosine can bind directly to histamine H 1 receptors . Furthermore, an H 1 receptor antagonist has been reported to induce reactive oxygen species (ROS)‐dependent cytochrome c release and apoptosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miller and O'Dowd have reported that, like histamine, carnosine directly activates smooth muscle histamine H 1 receptors to provoke vasoconstriction, but induces vascular relaxation through H 2 receptors . Ligand–receptor binding tests revealed that carnosine can bind directly to histamine H 1 receptors . Furthermore, an H 1 receptor antagonist has been reported to induce reactive oxygen species (ROS)‐dependent cytochrome c release and apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…27 Ligand-receptor binding tests revealed that carnosine can bind directly to histamine H 1 receptors. 28 Furthermore, an H 1 receptor antagonist has been reported to induce reactive oxygen species (ROS)-dependent cytochrome c release and apoptosis. 29 Conversely, intracellular increases in cAMP induce a protein kinase A-dependent inhibition of ROS production 30 and intracellular cAMP levels can be upregulated by activation of H 2 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Given the potency of carnosine in the regulation of the vascular tone, it is thought that not only exogenously administered carnosine, but also endogenously available carnosine takes part in normal hemodynamic regulation. The formation in vivo of a zinc/carnosine complex and the involvement of histamine H 1 receptors appear to be involved in vascular smooth muscle contraction/relaxation (255,277). However, alternative vasoactive mechanisms of carnosine may be equally involved, such as the carnosine-histidine-histamine pathway (151), a NO/ cGMP mechanism (318), and the modulation of the autonomic nervous system (265).…”
Section: Carnosine In Cardiovascular Functionmentioning
confidence: 99%
“…This effect was specific to carnosine, as its constituent amino acids were ineffective, and is considered to be attributed to the zinc/carnosine complex ( 105 , 106 ). Other mechanisms of the antihypertensive action of carnosine may be mediated via the histamine H1 receptors ( 107 ) and the carnosine-histamine-histidine pathway ( 108 ). A summary of the research investigating the effect of exogenous carnosine, and its constituent amino acids, on hemodynamic parameters in animal models is displayed in Table 3 .…”
Section: Physiological Roles Of Carnosine In Myocardial Tissuementioning
confidence: 99%